2004
DOI: 10.1177/0193945904267734
|View full text |Cite
|
Sign up to set email alerts
|

Pain Assessment Practices With Nursing Home Residents

Abstract: The purpose of this research was to describe the kinds of pain assessments nursing home staff use with nursing home residents and the characteristics and behaviors of residents that staff consider as they assess pain. Twenty-one focus groups were held in 12 nursing homes. Nurses and other nursing home staff attended the focus groups. Coding techniques consistent with ethnographic methodology were used for data analysis. Four themes identified an underlying uncertainty in assessing residents' pain, the staff re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 24 publications
2
57
0
Order By: Relevance
“…This practice limits the degree to which future interventions can be individualized. Consistent with findings from other qualitative studies (Clark, L., Jones, K., Pennington, K., 2004; Parke, B., 1998; Kovach, Griffie, Muchka, Noonan, & Weissman, 2000), personal knowledge and the use of an individualized approach for addressing behavioral changes was identified by some nurses as particularly important for identifying and responding to hypoactive behavioral changes. Decision support systems capable of accommodating and even recommending individualized assessment and treatment approaches may be particularly useful as nurses’ described very little documentation of results from any approaches.…”
Section: Discussionsupporting
confidence: 83%
“…This practice limits the degree to which future interventions can be individualized. Consistent with findings from other qualitative studies (Clark, L., Jones, K., Pennington, K., 2004; Parke, B., 1998; Kovach, Griffie, Muchka, Noonan, & Weissman, 2000), personal knowledge and the use of an individualized approach for addressing behavioral changes was identified by some nurses as particularly important for identifying and responding to hypoactive behavioral changes. Decision support systems capable of accommodating and even recommending individualized assessment and treatment approaches may be particularly useful as nurses’ described very little documentation of results from any approaches.…”
Section: Discussionsupporting
confidence: 83%
“…Many participants in this study reported difficulties and limitations in recognising pain in residents with whom they were unfamiliar. Previous research reported similar findings for nurses and certified nursing assistants (CNAs) [34]. Interestingly, in the present study, most HCAs sought to gain insight into residents’ past pain experiences and behaviours through liaison with patients’ families, friends and other key health and social care staff.…”
Section: Discussionsupporting
confidence: 59%
“…However, participants’ narratives revealed that most regularly performed informal relationship-centred pain assessments as an inherent part of care provision. Such assessments occur when knowledge and understanding of patients’ normative patterns of behaviour, physical and cognitive functioning and past reactions to pain are used to inform recognition and interpretation of behavioural and nonverbal pain cues [34]. Daily care provision brought HCAs in this study into close physical and social contact with residents, allowing them to develop a comprehensive knowledge and understanding of their care-recipients over time [1922].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nurses were required to learn the meaning of the cues, because the impaired older adults could not verbalise what they wanted the nurses to know (Parke, 1998). A deeper level of knowing was achieved by some nurses who could interpret certain patients' non-verbal cues (Clark et al, 2004;Tutton and Seers, 2004).…”
Section: Proxy Reporting Of Pain Statusmentioning
confidence: 99%